KONSEP INDEPENDENSI KEJAKSAAN REPUBLIK INDONESIA DALAM PERSPEKTIF TEORI THE NEW SEPARATION OF POWER BRUCE ACKERMAN - Sarah Nur Annisa (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
Independence is a must in a state of law (rechtstaat) as stated in article 1 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The independence is inseparable from the theory of separation of powers. The separation of powers theory was developed by Charles Louis de Secondat Baron Montesquieu or better known as the trias politica theory which divides power into three, namely executive power, legislative power, and judicial power. The 1945 Constitution does not explicitly explain the existence of the prosecutor's office, but in Law no. 16 of 2004 which regulates the Attorney General's Office of the Republic of Indonesia places this institution as a